Shear-wave elastography in thyroid ultrasound: Can be a predictor of extrathyroidal extension and cervical lymph node metastasis in papillary thyroid carcinoma?. Issue 52 (24th December 2020) - Han, Dong Yoon; Sohn, Yu-Mee; Seo, Mirinae; Yun, Seong Jong; Park, Won Seo; Jeon, Seok Ho; Cho, Yong Hyun
Abstract : Abstract: This study aimed to investigate whether extrathyroidal extension (ETE) and cervical lymph node metastasis (LNM) can be predicted using elasticity parameters of shear-wave elastography (SWE) combined with B-mode ultrasound (US) of papillary thyroid carcinomas (PTCs). We retrospectively reviewed 111 patients who underwent preoperative SWE evaluation among PTC patients from July 1, 2016 to June 20, 2018. Patients were divided into 2 groups based on the presence or absence of ETE based on pathology reports. Univariate and multivariate analyses of clinical and radiologic features including B-mode US features, US patterns, and SWE parameters were performed. These analyses were repeated in LNM positive and negative groups. The diagnostic performance of SWE parameters were also evaluated. Of the 111 patients, 33 had ETE, 78 did not have ETE, 44 had LNM, and 67 did not have LNM. A taller-than-wide shape and T3 stage on US were associated with ETE. Female sex, total thyroidectomy, and T3 stage on US were associated with LNM. When B-mode US and SWE were combined, there was no improvement in diagnostic performance. Combination of SWE and B-mode US findings is not useful for predicting ETE and LNM status in PTC patients.